Quantitative Trait Loci Associated with Drought Tolerance in Common Bean. Issue 3 (1st May 2014) - Mukeshimana, Gerardine; Butare, Louis; Cregan, Perry B.; Blair, Matthew W.; Kelly, James D.
ABSTRACT: Drought stress is the major limitation of common bean ( Phaseolus vulgaris L.) grown in subsistence farming systems worldwide. The objective of this study was to use single nucleotide polymorphism (SNP) markers from the BARCBean6K_3 Beadchip to identify quantitative trait loci (QTL) associated with traits related to drought tolerance in common bean. An intergene pool recombinant inbred line (RIL) population from a cross of drought tolerant line SEA5 and CAL96 cultivar was evaluated in Rwanda for 3 yr under drought stress and nonstress and in Colombia for 1 yr under drought stress. Traits evaluated included the numbers of days to flower, maturity, and seed fill; harvest index and pod harvest index; yield and yield components including number of pods per plant, seeds per pod, 100 seed weight (SW), and seed yield per day. Harvest indices, and SW were stable regardless of water treatment while number of pods per plant, seeds per pod, and yield were significantly reduced by drought. A linkage map of the RIL population spanning 1351 cM was constructed using 2122 SNP markers. The map covered all eleven bean chromosomes with an average distance of 0.64 cM between markers. A total of 14 QTL for performance under drought were consistently identified in different environments. Quantitative trait loci associated with phenology and SW traits mapped near previously reported QTL. Linkage between SW and yield QTL SY3.3 SC was observed on Pv03 and could be used to simultaneously select for seed yield and size in intergene pool crosses of common bean.